O desenho livre e os processos de criatividade e imaginação na educação infantil - Souza, Alisson da Silva (2018)
This research, entitled The free drawing and the processes of creativity and imagination in Child Education, aims to understand the meanings attributed by the teaching subject to the drawing, as to investigate the conditions and the ways in which the work with the drawing and the arts are developed in the daily life of Early Childhood Education. The present study presents a resumption of the main conceptions developed about the drawing, focusing in the perspective of Lev Vigotski, author that we chose as main reference of this investigation. The choice of a qualitative methodology led us to the cartography method, based in the studies of Passos, Kastrup and Escóssia (2009), Kastup (2008 and 2013) and Barros e Silva (2013), both inspired by the philosophical Gilles Deleuze and Felix Guattari (1995). There are four participants in this research, two teachers from the year 4 and two from the year 5 from Madre Maria Goretti Nery Municipal School, located in Santo Antônio de Jesus, in the state of Bahia. The instruments used to construct the data in the research field were: a) participant observation; b) interventions through workshops; and c) field diaries; d) photographic records. The results point out that the work with drawing and the arts in Early Childhood Education finds difficulties with regard to the organization of curriculum and routine, which prioritizes the pedagogical aspects of learning in spite of aesthetic aspects; the lack of materials and resources to work with the arts in general, and the insufficient training of teachers to work with drawing. The workshops favored the teachers’ experiences, so the interventions promoted living spaces and reflections on the meanings of drawings, as well as their relevance in daily practice in Early Childhood Education. The results also point out that the teachers' practices in relation to drawing are closely associated with the dimension of meaning and that classroom experiences are usually conditioned by the representation of the real meaning of the drawing.Thus, we highlight the need for the Infant Education routine reorganization in relation to the forms and uses of drawing, as well as for a specific training network, focused on the aesthetic meanings of the arts and design to promote teachers consciousness about the importance that artistic aspects play in educational processes, recognizing creativity and imagination in childhood as part of the process of constitution of the human factor